Scaling-up public sector childhood diarrhea management program: Lessons from Indian states of Gujarat, Uttar Pradesh and Bihar - Sanjeev Kumar; Rajashree Roy; Sucharita Dutta (Edinburgh University Global Health Society, 2015)
Diarrhea remains a leading cause of death among children under five in India. Public health sector is an important source for diarrhea treatment with oral rehydration salts (ORS) and zinc. In 2010, Micronutrient Initiative started a project to improve service delivery for childhood diarrhea management through public health sector in Gujarat, Uttar Pradesh (UP) and Bihar. This paper aims to highlight feasible strategies, experiences and lessons learned from scaling-up zinc and ORS for childhood diarrhea management in the public sector in three Indian states. The project was implemented in six districts of Gujarat, 12 districts of UP and 15 districts of Bihar, which includes 10.5 million children. Program strategies included capacity building of health care providers, expanding service delivery through community health workers (CHWs), providing supportive supervision to CHWs, ensuring supplies and conducting monitoring and evaluation. The lessons described in this paper are based on program data, government documents and studies that were used to generate evidence and inform program scale-up. 140 000 health personnel, including CHWs, were trained in childhood diarrhea management. During three years, CHWs had sustained knowledge and have treated and reported more than three million children aged 2-59 months having diarrhea, of which 84% were treated with both zinc and ORS. The successful strategies were scaled-up. It is feasible and viable to introduce and scale-up zinc and ORS for childhood diarrhea treatment through public sector. Community-based service delivery, timely and adequate supplies, trained staff and pro-active engagement with government were essential for program success.